(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The purpose of this paper is to examine the scope of the CJEU’s and ECtRH’s standards of protection of same-sex relationships as new modern realities of family life and the same-sex couples’ rights, insofar as it concerns human rights – the right to private and family life, dignity, equality and non-discrimination. The legal regulation of same-sex relationships as a family law issue is primarily matter of national law. Consequently, the divergent views on this issue in national jurisdiction raise complex questions requiring adequate answers and clear standards at EU and International (Convention) levels. Therefore, the author (by case study method, normative and comparative analyses) gives an overview of the progress of the protection of same-sex couples’ rights on the national level, with particular reference to the Republic of Croatia but also at EU and Convention levels. The paper focuses on the CJEU and ECtRH case law as regards the same-sex relationships and same-sex couples’ rights and offers landmark cases with an analysis of the most recent judgments. In connection to the latter, a brief discussion of the nature of EU and Convention legal orders and the role of two European Courts within these legal orders is given as well as their interrelation on this issue. The paper will try to provide an answer to the question how the EU and Conventional law standards that have been established regarding the legal recognition of same-sex relationships and protection of same-sex couples rights influenced a national constitutional standard, with an analysis of two most important decisions of the Constitutional Court of the Republic of Croatia directly concerning the same-sex couples rights.